2003
DOI: 10.1159/000069388
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric and Portal Vein Gas: Computerized Tomography Findings and Clinical Significance

Abstract: Background: Gas in the mesenteric or portal veins (PVG) is an uncommon entity. It was first described only in patients with mesenteric ischemia and bowel gangrene. Later, several reports described other causes for PVG in which conservative treatment was successful. In the past, the diagnosis was made by vague signs in abdominal plain films. Since the era of computerized tomography (CT) scan the diagnosis became more objective, but nevertheless it is still an elusive entity. Our objective was to relate clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…The combination of PI and PVG has previously been reported to have high fatality rate and typically; 70% of patients with PI and PVG have bowel ischemia. 17,18 In addition, we found that surgically treated PI patients with PVG (Fig. 1a) had a slightly decreased risk of death (p>0.05) compared to other PI patients, and we suggest that these patients should be considered for surgical intervention.…”
Section: Discussionmentioning
confidence: 65%
“…The combination of PI and PVG has previously been reported to have high fatality rate and typically; 70% of patients with PI and PVG have bowel ischemia. 17,18 In addition, we found that surgically treated PI patients with PVG (Fig. 1a) had a slightly decreased risk of death (p>0.05) compared to other PI patients, and we suggest that these patients should be considered for surgical intervention.…”
Section: Discussionmentioning
confidence: 65%
“…In case of surgical illness, early intervention is vital because a delay significantly increases mortality. 4 In our case, the presence of an acute abdomen, HPVG and CT scan findings suggestive of intestinal ischemia necessitated exploratory laparotomy.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, presence of portal venous gas seems to be suggestive of bowel ischemia This is in agreement with suggestions made by some authors that the combination of PI and portal venous gas is associated with bowel ischemia in about 70% of cases. [16][17][18] It is necessary to identify factors responsible for poor prognosis and high mortality and to make a decision regarding surgical intervention, if needed, early to avoid life-threatening complications resulting from bowel perforation and resulting peritonitis. It is imperative that imaging findings of PI are carefully correlated with clinical history, abdominal signs, and blood work indicating any metabolic derangement to differentiate patients who need surgical intervention from those who can be treated conservatively.…”
Section: Discussionmentioning
confidence: 99%